Building And Analyzing The Use Of Network Systems In Diskless-Based Intro Internet Café - Abid Rusidi; Khairil; Arius Satoni Kurniawansyah (Jurnal Komputer, Informasi dan Teknologi, 2024)
The use of computers and internet has become an integral part of daily life. A popular use is online gaming, where access convenience is often lower through smartphones compared to computers, leading many gamers to continue using their computers or visit internet cafes to meet their gaming needs. The success of internet cafes also depends on internet speed and computer device maintenance. The process of updating games on each client computer also affects overall internet speed. To address this issue, Intro internet cafe has built a diskless-based system, which centralizes data on the server so that game updates only need to be done on the server, allowing users to access the latest version without manual updates on each client computer, while also having sufficient security. This research aims to build and analyze the use of network systems in Diskless-Based Intro internet cafe. With a focus on configuration, performance, and efficiency, this research addresses several issues that arise with the use of diskless systems. The results show that the diskless system provides many benefits, such as reducing hardware costs, easier management, and increased data security. This system allows client computers to boot via the network and efficiently run the operating system. It is expected that the implementation of a diskless system in the operations of Intro internet cafe will provide efficiency and significant benefits.